2021
DOI: 10.35787/jimdc.v10i1.577
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Near-Peer Tutoring in Small Group Discussions: A Pilot Study

Abstract: Background: A year senior medical students can prove to be a useful teaching resource with added benefits for the tutors. The objective of this study was to explore the perceptions of near-peer tutors after facilitating small group discussions while delivering an integrated curriculum in preclinical years. Material and Methods: This qualitative exploratory pilot study was conducted in Rawal Institute of Health Sciences Islamabad, Pakistan from July 2017 to November 2017. Students of First year MBBS class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, 90% of the NPMs also agreed that their confidence and communication skills were improved during this study. This was consistent with the studies by Abdolalizadeh et al [11] and by Muazam et al [21] in which it was evident that near-peer mentoring brought a positive change in students' professional abilities like communication, leadership, and facilitation. The reason can be that they were networked and managed the diverse groups of mentees solely and this led to an increase in motivation to complete their course with more dedication.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, 90% of the NPMs also agreed that their confidence and communication skills were improved during this study. This was consistent with the studies by Abdolalizadeh et al [11] and by Muazam et al [21] in which it was evident that near-peer mentoring brought a positive change in students' professional abilities like communication, leadership, and facilitation. The reason can be that they were networked and managed the diverse groups of mentees solely and this led to an increase in motivation to complete their course with more dedication.…”
Section: Discussionsupporting
confidence: 92%
“…Muazam et al also reported that the PAL technique creates an atmosphere that allows the learners to achieve goals in a stress-free manner. 12 Burgess et al also reported that PAL provided a respectful learning environment for the students with different abilities. 13 The PAL program was highly valued by the studenttutors with measurable benefits to the learners.…”
Section: Discussionmentioning
confidence: 99%
“…One of the students stated, "teaching is a technique and a skill". 12 The student tutors commented positively on the quality of the learning experience with their peer tutors. The tutors felt motivated to take the task as they believed they had the confidence to lead the team.…”
Section: Discussionmentioning
confidence: 99%